Root Couse Analysis (RCA) and Plan Internal Quality Audit Results Corrective Action - Sarlota Singerin (International Journal of Education, Information Technology, and Others, 2021)
Nationally, the quality of secondary education in Indonesia has not been as expected. The results of the quality mapping based on data from the Directorate General of Primary and Secondary Education show that only about 16% of education units meet the National Education Standards (SNP). Most of the other education units have not met the SNP, in fact there are a number of education units that still do not meet the minimum service standards (SPM). This study aims to: describe the quality management, find the causes and root problems associated with the findings of the Internal Quality Audit and provide recommendations and suggestions on corrective measures that can be used as solutions to problems found at YPKPM Ambon Christian Senior High School. This study uses the Root Cause Analysis method "5 why analysis" by asking why 5 times or repeatedly to find the root of a problem. The results of this study found that the root causes are: 1). almost some teachers do not understand what is an internal quality audit; 2). there is no disclosure of the findings of the internal quality audit; 3). Management School management is not based on quality report cards. Action plans to improve the results of the Internal Quality Audit that must be carried out are: socializing the internal quality audit instrument and restructuring the supporting documents for the audit instrument and school management based on quality report